Scaling Sustainable Packaging in International Market: A case study from Nepal - Sagar, Shrestha; Janaki Devi, Chaudhary (My University, 2026)
Global sustainable packaging market is projected to expand in huge volumes by 2030 which is driven by tightening regulations like PPWR and growing consumer demand. This situation creates real opportuni ties, but also serious structural difficulty for SMEs in landlocked developing countries like Nepal. Despite the fact that Nepal has natural advantages in indigenous fibres, fast regenerating plant resources and traditional craft skills, prevailing deep institutional and logistical barriers block international market access. This study examines how Nepalese sustainable packaging firms navigate barriers to internationalisation and scaling. For this, data came from the semi structured interviews with representatives from ten firms. The firms work with different materials including biopolymers, natural fibres, biocomposites, recycled materials and leaf based tableware and one logistics firm was also included to capture export infrastructure constraints. The analyses is based on GVC theory and Sustainable Entrepreneurship theory with SBMC as organizing structure for cross comparison. Three findings emerge from this study. First, barriers are not isolated. Economic, technical, institutional and logistics constraints form compounding loops whose severity depends on a firm’s material type. Second, material choice functions as metastrategy producing three distinct archetypes: heritage craft positioning, technologydependent scaling and circular systemic positioning, each with a different barrier profile and growth pathway. Third, a willingnesstopay paradox characterises the domestic market: consumers accept modest price premiums, but actual sustainable production costs are far higher, pushing viable firms toward international premium markets. The binding constraint on scaling is not entrepreneurial capacity. It is the gap between firmlevel achievement and institutional ecosystem support. This requires shared certification infrastructure, coordinated logistics, growthstage financing and integrated policy coordination.
Keywords: sustainable development; entrepreneurship; small and medium-sized enterprises; nepalilaiset; marketing; logistics; internationalisation; export; value chains; green economy; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management